2017
DOI: 10.1248/cpb.c17-00123
|View full text |Cite
|
Sign up to set email alerts
|

Naphtoquinones and Sesquiterpene Cyclopentenones from the Sponge <i>Smenospongia cerebriformis</i> with Their Cytotoxic Activity

Abstract: Two new naphtoquinones (smenoceronesMarine sponges have produced a huge variety of secondary metabolites in which approximate 300 new structures were reported annually in the past decade.1-3) Sponge derived compounds are not only displayed unique chemical structures but also interesting biological properties and made sponges become a potent source of lead compounds for new drug discovery.1,4) Sponge genus Smenospongia (order Dictyoceratida, family Thorectidae) has been found comprising 19 species. Especially, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…Accordingly, the absolute configuration of C-16, C-17 of dactylospongenon A-D compounds (71-74) were determined as (16R,17S), (16S,17R), (16R,17R) and (16S,17S), respectively. [32] The merosesquiterpene 57-74 were evaluated for their cytotoxic and antiinflammatory effects. The results showed that compound 70 exhibited very promising cytotoxic effect with IC50 values of 1.10, 1.62, 0.65, 1.33, and 0.73 µg/mL against LU-1, MCF-7, HepG2, SK-Mel2, and HL-60, respectively.…”
Section: Sesquiterpenesmentioning
confidence: 99%
“…Accordingly, the absolute configuration of C-16, C-17 of dactylospongenon A-D compounds (71-74) were determined as (16R,17S), (16S,17R), (16R,17R) and (16S,17S), respectively. [32] The merosesquiterpene 57-74 were evaluated for their cytotoxic and antiinflammatory effects. The results showed that compound 70 exhibited very promising cytotoxic effect with IC50 values of 1.10, 1.62, 0.65, 1.33, and 0.73 µg/mL against LU-1, MCF-7, HepG2, SK-Mel2, and HL-60, respectively.…”
Section: Sesquiterpenesmentioning
confidence: 99%
“…Theo đó, cấu hình tuyệt đối ở C-16, C-17 của các hợp chất 280-283 lần lượt được xác định là (16R,17S), (16S,17R), (16R,17R) và (16S,17S). [72] Các merosesquitecpen 266-283 được đánh giá tác dụng gây độc tế bào và tác dụng kháng viêm. Kết quả cho thấy hợp chất 279 thể hiện tác dụng gây độc tế bào ung thư rất triển vọng với giá trị IC 50 là 1,10, 1,62, 0,65, 1,33 và 0,73 µg/mL lần lượt tương ứng với các dòng tế bào LU-1, MCF-7, HepG2, SK-Mel2 và HL-60.…”
Section: Nhóm Chất Sesquitecpenunclassified
“…Kết quả đánh giá tác dụng gây độc tế bào cho thấy hợp chất 316 gây chết các tế bào ung thư LU-1, HepG-2, HL-60, MCF-7 và SK-Mel-2 với các giá trị IC 50 lần lượt là 5,5, 3,2, 4,0, 4,1 và 5,7 µg/mL. [72] Bên cạnh đó một hợp chất furanoterpen mới và bốn hợp chất đã biết với cấu trúc hóa học mạch chính 21 cacbon hoặc 25 cacbon cũng được phân lập từ loài hải miên Ircinia echinata như 8hydroxyisovariabilin (317), (12E,20Z,18S)-8hydroxy-variabilin (318), (7E,12E,20Z,18S)variabilin (319), (7E,3S)-11-hydroxy-3,7,11trimethyl-14-(furan-3-yl)-tetradec-11-enoic acid (320), (7E,11E,3S)-3,7,11-trimethyl-14-(furan-3-yl)tetradeca-7,11-dienoic acid (321). [24,85] Một số các hợp chất chứa brom trong phân tử cũng được phân lập từ một số loài hải miên như purealidin R (322), fistularin-3 (323) phân lập từ loài hải miên Ianthella basta; [86] xestospongiene A (324) và xestospongiene J (325) phân lập từ loài hải miên Haliclona oculata; [21] hay hợp chất 3,5-dibromo-1-hydroxy-4,4-dimethoxy-2,5-cyclohexadiene-1-acet-amide (326) phân lập từ loài hải miên Acanthella obtusa.…”
Section: Một Số Nhóm Chất Khácunclassified
“…Recently reports on biological activity substances of sponge growing in Vietnam waters mainly on alkaloids, terpenoids and steroids belong to different sponge species for instance Aaptos suberitoides [10,11], Petrosia nigricans [12], Dysidea cinerea [13], Dysidea fragilis [14,15], Smenospongia cerebriformis [16,17], Haliclona oculata [18], and bioactivities of them were showed including the toxic [16,18], anti-inflammatory [17], anti-bacterial [19], and anti-cancer activity [10,11]. There are not any report on antioxidant activity of marine sponges in Vietnam waters.…”
Section: Introductionmentioning
confidence: 99%